Population dynamics of Phaius flavus in southeast China: Reproductive strategies and plants conservation. - Jun Li; Ya-Ting Zhu; Lun-Yan Chen; Ai-Xian Lu; Hong-Yu Ji; Hai-Ping Liu; Ze-Xin Li; Zuo-Dong Lin; Sha-Sha Wu; Jun-Wen Zhai (PLoS ONE, 2022)
Because of species diversity and troubling conservation status in the wild, Orchidaceae has been one of the taxa with most concern in population ecological research for a long time. Although Orchidaceae is a group with high adaptability, they have become endangered for complex and various reasons such as the germination? difficulty and habitat loss, which makes it difficult to develop an accurate protection strategy. Phaius flavus is a terrestrial orchid which used to be widely distributed in central and southern Asia; however, large populations are difficult to find in the wild. Thus, the aim of this study was to provide a new perspective for conserving endangered P. flavus by investigating the mechanisms of its population decline; we established time-specific life and fertility tables, age pyramids, survival curves, and mortality curves for this plant and then conducted Leslie matrix model. We found that both of the populations from Wuhu Mount (WM) and Luohan Mount (LM) showed declining trends and exhibited pot-shaped age pyramids, low net reproductive rates, and negative intrinsic growth rates. The population from the Beikengding Mount (BM) showed a stable status with a bell-shaped age pyramid. However, it has a significant risk of decline because of the low net reproductive rate and intrinsic growth rate. This study use time-specific life and fertility tables, age pyramids, survival curves, and mortality curves, showed that the population decline of P. flavus could be attributed to 1) the shortage of seedlings caused by the low germination rate in the wild and 2) the loss of adult individuals caused by anthropogenic disturbances. To protect this species from extinction in these areas, we suggest that human activities in these habitats should be strictly forbidden and ex situ conservation of this plant in botanical gardens is also necessary.